The role of the dietary patterns in the cardiovascular disease risk prevention (Journal of Medical Science, 2022)
Cardiovascular diseases (CVD) are a part of a wide group of diseases, which became main threat to the life and health of the population in highly developed countries. To prevent and treat CVD, in addition to implementation of pharmacological methods, there are a number of lifestyle components, including eating habits, that significantly influence the development of these diseases. The dietary patterns strongly correlate with the risk of cardiovascular disease. Modifications of the dietary habits allow to control many parameters such as: body weight, cholesterol/triglyceride levels or blood pressure. Alternative diets are frequently used to reduce the risk of developing a CVD. The main recommended dietary patterns includes Mediterranean diet (MD), the DASH diet (Dietary Approach to Stop Hypertension) and mild variants of vegetarianism. The more controversial nutritional styles includes the ketogenic or vegan diets. Due to various assumptions as well as the mechanisms of action of each diets, an attempt of its evaluation have been made. The aim of our study is to review and analyze the available data on the impact of various nutrition models regarding to cardiovascular diseases risk prevention.